2019
DOI: 10.6065/apem.2019.24.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aspects of type 1 diabetes

Abstract: Type 1 diabetes mellitus (T1DM) is characterized by autoimmune destruction of pancreatic beta-cells in genetically predisposed individuals, eventually resulting in severe insulin deficiency. It is the most common form of diabetes in children and adolescents. Genetic susceptibility plays a crucial role in development of T1DM. The human leukocyte antigen complex plays a key role in the pathogenesis of T1DM. Furthermore, genome-wide association studies and linkage analysis have recently made a significant contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 64 publications
3
14
0
2
Order By: Relevance
“…In a large analysis of the T1D population in all Brazilian regions, a result similar to ours was found 46 . It is reported that approximately 30% of individuals with T1D have DR3/DR4 in heterozygosity 6,47 , corroborating our ndings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a large analysis of the T1D population in all Brazilian regions, a result similar to ours was found 46 . It is reported that approximately 30% of individuals with T1D have DR3/DR4 in heterozygosity 6,47 , corroborating our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…Certain combinations of alleles are found in speci c haplotypes of the HLA-DRB1~DQA1~DQB1 genes, varying between some ethnic groups, conferring susceptibility or protection to the disease 3,4,5 . In Europeans, the greatest risk to the disease is associated with the haplotypes DRB1*04:01/02/04/05~DQA1*03~DQB1*03:02 and DRB1* 03:01~DQA1* 05:01~DQB1* 02:01 1,6,7 . In patients of African origin, additional haplotypes are associated with risk, such as DRB1 * 09: 01~DQA1* 03:01~DQB1* 02:01 and DRB1* 07:01~DQA1* 03:01~DQB1* 02:01 8 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, of the 45 tagSNPs focused on inferring classic HLA alleles, 14 showed statistically significant association (Table 4). The association was more significant for the tagSNPs of the class II alleles than for the class I alleles, which is consistent with the literature 30‐32 . SNP rs2187668 (tagSNP for haplotype DQ2.5) and rs7454108 (tagSNPs for haplotype DQ8) have been found associated with susceptibility to T1D and also with other autoimmune diseases 33 in various populations worldwide 34,35 .…”
Section: Discussionsupporting
confidence: 89%
“…The association was more significant for the tagSNPs of the class II alleles than for the class I alleles, which is consistent with the literature. [30][31][32] SNP rs2187668 (tagSNP for haplotype DQ2.5) and…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the variation of the DNA methylation within the INS gene is suspected to regulate INS gene transcription in the pancreatic β-cells as well as the medullary thymic epithelial cells. These two tissues are known to be the sites where INS gene is expressed and to be the center of the mechanisms of T1D (43). One study highlighted the relationship between the immune response the DNA methylation changes at Ins1 and Ins2 genes that occurs in both β-cells of non-obese diabetic mice and human β-cells (41).…”
Section: Epigenetics In T1dmentioning
confidence: 99%